Entre a utopia do reequilíbrio de interesses e a factualidade da anomalia funcional do direito autoral na cibercultura: as licenças Creative Commons como estratégia ambivalente - Soares, Matheus Victor Sousa (2021)
The purpose of this work is to clarify how Creative Commons licenses are part of strategies for the adjustment of the Brazilian Copyright Law to the Cyberculture scenario. This digital context explains the anomalous function of the Copyright Law, once the forms of sociality of cyberspace imply in multiple forms of creation and sharing of authorial work which, in a conjuncture where the sense of conservation of structures exclusively directed to the economic exploitation of the so-called intellectual property prevails, unleash illegal acts committed under the flag of the need of compulsory accomplishment of the principle of social function by the users themselves, which represents problems. Creative Commons licenses emerge as an alternative to this unbalanced situation, proposing a redistribution of power over the creation and dissemination of works. They endorse the author-society bond - understood in this expression also as intermediary instances (editors, producers, agents) - through the attribution of self-government tools parallel to the national authorial legislation and to the strictness of the international conventions, being apparently propitious, at the same time, to the accomplishment of fundamental rights and to the exercise of secular authorial prerogatives, in the flexible digital field. Therefore, we start from the question: what is the author-society balance sought and achieved by Creative Commons licenses in face of the interconnections of cyberculture? It is considered, as a hypothesis, that Creative Commons licenses create, a priori, a certain degree of leveling between the subjects of the creative circularity, thus rebalancing the legal relationships involving the work; they perform, in addition, a certain conciliatory function of the interests involved in the creation and circulation of works in any environment, real or digital. Methodologically, to answer this research problem, the documental and bibliographic techniques are used, starting from the analysis of scientific articles, theses, dissertations of the hybrid branches of Copyright and Digital Rights, going through contemporary communication theorists. This approach resulted in the perception that for the development of a Copyright Law of Cyberculture it is necessary to elaborate ambivalent strategies, which means, at the same time, solve sporadic crises and may promote and conduct the debate of the public sphere for the correction of the functional anomaly, aiming at assuring the social function of this segment of the Law connected to the management of creativity. It was observed that Creative Commons licenses integrate these strategies, but are not enough to by themselves and isolated from other mechanisms, overcome the adversities imposed by the Cyberspace to Copyright. It was learned, thus, that it is necessary to distinguish the Creative Commons licenses, as legal instruments that serve palliative functions, from the Creative Commons Brazil, in the condition of civil society organization capable of actively confronting - in coordinated actions with other sectors and entities - the functional anomaly of the Brazilian Copyright Law. The present study emerges to give a contribution to the paradigmatic revolution that is coming and provides an opportunity for the Copyright Law to deal seriously with its tormented paradoxes.